Integrasi Kearifan Lokal dalam Pembelajaran Matematika Dasar pada Mahasiswa - Fitri Rezkiamaliah; Abdul Majid (Lembaga Yasin AlSys, 2026)
Basic Mathematics learning is still generally understood as a formal calculation activity that is disconnected from students’ managerial needs, social lives, and cultural values. This condition indicates the need for a learning model that integrates numeracy competencies with students’ sociocultural contexts. This study aims to formulate a model for integrating local wisdom into Basic Mathematics learning for students of the Islamic Education Management Study Program at STAI DDI Pangkep. The study employed a descriptive qualitative approach using an integrative literature review and contextual analysis. The data sources consisted of 35 scholarly articles published between 2020 and 2025 that discussed ethnomathematics, numeracy literacy, local wisdom-based learning, and the value of siri’ na pacce in education. The data were analyzed through the stages of theme identification, concept categorization, critical synthesis, and the formulation of an implementable model. The results indicate that the integration of local wisdom can be implemented through four main patterns: contextualizing materials on numbers, percentages, ratios, basic statistics, and mathematical logic; using sociocultural cases from Pangkep; strengthening the value of siri’ na pacce in the learning process; and implementing project-based numeracy assessment. This integration has the potential to strengthen numeracy literacy, logical reasoning, academic honesty, responsibility, and decision-making skills among Islamic Education Management students. This study concludes that local wisdom-based Basic Mathematics learning can serve as a contextual approach that connects numeracy competencies with Islamic values and Bugis-Makassar culture. These findings provide a conceptual contribution to the development of contextual mathematics learning and practical implications regarding the need to systematically develop local wisdom-based Basic Mathematics modules.